1/6x-3=3/2x

Simple and best practice solution for 1/6x-3=3/2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6x-3=3/2x equation:



1/6x-3=3/2x
We move all terms to the left:
1/6x-3-(3/2x)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: 2x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
1/6x-(+3/2x)-3=0
We get rid of parentheses
1/6x-3/2x-3=0
We calculate fractions
2x/12x^2+(-18x)/12x^2-3=0
We multiply all the terms by the denominator
2x+(-18x)-3*12x^2=0
Wy multiply elements
-36x^2+2x+(-18x)=0
We get rid of parentheses
-36x^2+2x-18x=0
We add all the numbers together, and all the variables
-36x^2-16x=0
a = -36; b = -16; c = 0;
Δ = b2-4ac
Δ = -162-4·(-36)·0
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-16}{2*-36}=\frac{0}{-72} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+16}{2*-36}=\frac{32}{-72} =-4/9 $

See similar equations:

| 6=1-1n+5 | | 8x-1+4x=15 | | 1/2x-10=70 | | 6x-7+3x=12 | | -t+2+10t=8t-5 | | 16−2=1.5t+9 | | 3w+8-w=4w-2(w-4 | | 8k=6+5k | | -241-4x=74-13x | | 10x-5=8x=13 | | 6m-3=7m+-m | | 4-9h=-8-7h | | 1200=1.10b+2.5b | | 2(m-3+8=3m-8 | | -8(-4x+13)=17x-7(2x-10) | | 1/3y+5=13 | | -9-10m=6-7m+6 | | 16x+26+20x+40=24x-146 | | -8d-9=-6d+9 | | 6.4u-5.1u=3.25 | | (12x)+10x+20=180 | | 3/2a-8=18 | | 2y-5+10y=10y=9 | | 3x+3x+3=3 | | p-5=2p | | 3x3x+3=3 | | 5+10u=9u | | x/3x+1=3x-6/9x-2 | | 2(x-4)+8=4x | | 1=5g-9=7g-6 | | 1-2z=8-9z | | -10v-7=-9v |

Equations solver categories